Numerical Modeling Investigation of Irregular Wave Interaction with Perforated Caisson Breakwater - Rouhollah Amirabadi; Ahmad Rezaee mazyak; Ali Ghasemi (نشریه مهندسی دریا, 2018)
Caisson breakwater is one the most common coastal protection structures which their main application is to reduce wave energies and create a calm basin for berthing of the ships in ports. A simple approach to achieve this is to build a solid wall against the waves which are know as caisson breakwater. In this paper interaction of irregular waves with normal and perforated-wall caisson breakwater using FLOW-3D is studied. In this paper, the appropriate numerical model has been selected and then the model setup is explained. After the model setup, sensitivity analysis, calibration and verification of the model results with available laboratory data are presented. When the model performance is verified, the interaction of irregular wave with the perforated-wall caisson breakwaters is evaluated. The modeling results show that the perforated caisson breakwater compared to the vertical breakwater has a better hydraulic performance. In comparison to perforated-wall caisson breakwater results and euro top 2016 results, define a new dimensionless number to consider width of chamber to be recommended.